A Dynamic Investment Model with Profit-Sharing in an Interest-Free Economy: Methodological Issues (American Journal of Islam and Society, 1991)
The present paper is a contribution to the building blocks of an investmentmodel within the framework of an integrated macroeconomic model of anIslamic economy. Investment behavior in the model is guided by an Islamicethicalvalue system and profit-sharing financial contracts. The typical firm’sinvestment decision is believed to emerge from a dynamic inter-temporalmaximization exercise within an infinite time horizon. The method of Calculusof Variations is applied to arrive at the optimal investment and employmentcriteria for the firm. The result is then incorporated into a macroeconomicmodel to study the behavior of key endogenous variables like national incomeand the rate of profit-share. Comparative statics exercised within a generalequilibrium framework reveal the potency of monetary policy but the neutralityof fiscal policy with respect to output and employment.IntroductionThe past decade has witnessed a tremendous outpouring of interest aswell as effort in the formalization of economic models based on profit-sharingfinancial arrangements as an Islamic alternative to the conventional interestbasedeconomic system. Several macroeconomic models for interest-freeeconomies have been proposed (Anwar 1987; Habibi 1987; Metwally 1981& 1983). The rigor of an integrated approach to such macroeconomic modelhgdepends on the rigor of the component models, namely, the consumption,investment, monetary, and fiscal relationships. Economists have writtenextensively on different aspects of consumer behavior in Islamic societies.Kahf (1978) and Khan (1984), among others, have contributed to the conceptualand analytical formulation of the consumption function under ...